The Effect of Corrective Exercises on Some Biomechanical Variables and the Performance of the Hand Jump Skill in the Junior Category - Rahim, Fatima; Abdulredha, Bushra (Journal of Physical Education, 2025)
The study aimed to highlight the importance of corrective exercises and to address the development and status of athletic activities. It also emphasized the significant role of human movement in the successful execution of various sports performances. Furthermore, the study explored the field of biomechanics and its relationship to optimal performance through motion analysis. The significance of this research lies in designing corrective exercises for a selected sample group with the intention of improving their performance, overcoming technical faults, and achieving better athletic results. The front handspring skill on the floor exercise mat is considered one of the most difficult techniques for athletes, due to its requirements for technical precision and motor coordination. During a particular phase of the skill, the body reaches a handstand position, necessitating accurate synchronization between the force exerted by the hands against the ground and the moment the body’s center of gravity passes through the imaginary vertical axis.